An Overview of Spike Surface Glycoprotein in Severe Acute Respiratory Syndrome–Coronavirus - Kathiravan, Muthu Kumaradoss; Radhakrishnan, Srimathi; Namasivayam, Vigneshwaran; Palaniappan, Senthilkumar (Frontiers in Molecular Biosciences, 2021)
The origin of the novel coronavirus by December 2019 marked its existence in the province of the city Hubei, P.R. China. This contagious disease named as COVID-19 resulted in a massive expansion within six months by spreading to more than 213 countries. Despite the available antiviral drugs for the treatment of various viral infections, it was concluded by the WHO that there is no medicine till date to treat novel CoV, SARS-CoV-2. By the 21st century, it is identified that SARS-COV-2 is the most highly virulent human coronavirus and occupies the third position following SARS, MERS CoVs, with the highest mortality rate. The genetic assembly of SARS-CoV-2 is segmented into structural and non-structural proteins, of which two-third of the viral genome encodes non-structural proteins and the remaining genome encodes structural proteins. The most predominant structural proteins that make the SARS-CoV-2 include spike surface glycoprotein (S), membrane protein (M), envelope protein (E), and nucleocapsid protein (N). This review will focus on one of the four major structural proteins in the CoV assembly, the spike which is involved in the host cell recognition, fusion process and is one of the promising targets. The monomer disintegrates into S1 and S2 subunits with the S1 domain necessitating binding of the virus to its host cell receptor and the S2 domain mediating the viral fusion. On viral infection by the host, the S protein is further cleaved by protease enzyme to two major subdomains S1/S2. Spike is also proved to be an interesting target for developing vaccines and in particular, RBD-single chain dimer has shown initial success. The availability of small molecules and peptidic inhibitors for the host cell receptors is discussed in brief. The development of new molecules and therapeutic druggable targets for SARS-CoV-2 is of global importance. Attacking the virus employing multiple targets and strategies is the best way to inhibit the virus. This article will appeal to the researchers in understanding the structural and biological aspects of S protein in the field of drug design and discovery.